2018
DOI: 10.1111/cen3.12489
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of subtypes of multiple sclerosis and the most common clinical symptoms in Iranian patients: A meta‐analysis

Abstract: Multiple sclerosis (MS) is an inflammatory disease defined by damage to the myelin sheaths of neurons. MS is classified into different subtypes including relapsing–remitting MS, secondary progressive MS and primary progressive MS. The present study aimed to estimate the prevalence of different forms and clinical symptoms of MS among Iranian people using meta‐analysis. We searched all available databanks, such as SID, Magiran, PubMed, Google scholar, Scopus and Science, directly to identify relevant evidence. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…The prevalence of MS in Iran has been estimated at about 30 cases per 100,000 people 28 . It has been reported that approximately 70% of Iranian MS patients suffer from the relapsing‐remitting type 29 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of MS in Iran has been estimated at about 30 cases per 100,000 people 28 . It has been reported that approximately 70% of Iranian MS patients suffer from the relapsing‐remitting type 29 …”
Section: Methodsmentioning
confidence: 99%
“…28 It has been reported that approximately 70% of Iranian MS patients suffer from the relapsingremitting type. 29…”
Section: Study Population and Settingmentioning
confidence: 99%
“…Unlike aforementioned neurodegenerative diseases, MS happens usually in the age group of 20-50 and can affect children too [41]. MS is of four types -1) Relapsing-Remitting MS which is distinguished by the occurrence of acute deterioration in function followed by partial or total recovery [42,43]. 2) Severely deteriorated patients enter into Second Progressive MS stage which can be distinguished with the features as tiredness, rigidity, weakness, intestinal disorder, urinary disorder and psychological damage [44,45].…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Multiple sclerosis (MS) is a multifactorial, autoimmune and inflammatory disorder in the CNS characterized by demyelination, inflammation, and neurodegeneration which is one of the main causes of disability among young adults [1] [3] . Clinical manifestations of MS include paresthesia, diplopia, visual impairment, fatigue, emotional instability and hypoesthesia [4] , [5] . In developed cases, sever paresthesia affects upper and lower limbs [5] .…”
Section: Introductionmentioning
confidence: 99%